การศึกษาพฤติกรรมการมีส่วนร่วมในรายการโทรทัศน์การศึกษาเชิงโต้ตอบของเยาวชนในกรุงเทพมหานคร - สุรีย์พร บุญสมภาร (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purposes of this research were to study youth’s exposure, behaviors, and attitude in educational interactive television and to study the trend of using communication technology in educational interactive television. The samples were 403 youths aged between 11-24 years old in Bangkok metropolis and 9 producers of educational interactive television programs. Data were collected by questionnaires and structured interview form and content analysis were used to analyze qualitative data. The statistics used to analyze data were frequency, percentage, Phi, t-test, and ANOVA. The research of this research were as follows: 1.The sample exposed educational interactive television less than 3 times per week and mostly switched the program and others in the same time. Drama was the most frequency exposed type of educational interactive television; the others were game show and news. 2.Most of the sample used home telephones or PCTs and mobile phones for voting or texting message and voting via internet less than once a month. While using email and SMS for voting, they participated 1-3 times a month. Most of them participated in news programs for expressing their opinion, and participated in game show and documentary programs for inquiring more knowledge. 3.There were no any difference found in youth’s opinion in participation approach to educational interactive television with statistically significant at .05 level classified by gender, age, income, level of education, mobile phone expense, and home telephone expense. The sample with difference background had difference purposes of participation in chatting, expressing opinion, registering to the program, leaving questions, sending video clip, and complaining with statistically significant at .05 level. There was no difference found in the purposes of participation in contesting for the money or award and answering the questions or playing a game. The sample who had difference background except gender had difference attitude of participation in educational interactive television with statistically significant at .05 level. 4.Producers of educational interactive programs selected communication technologies by considering on comfortable and appropriate of audience budget and the open channels for all audiences.